PENGARUH LIMBAH PADAT KELAPA SAWIT (SLUDGE) DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) - Gustian Affandi; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of the interaction of sludge and phosphorus fertilizers and to obtain the best dose in increasing the growth and production of sweet corn (Zea mays saccharata Sturt) on inceptisol soil in experimental station of Faculty of Agriculture, University of Riau from January 2018 to March 2018 using Randomized Block Design (RAK) method consisting of two factors and three replications. The first factor was solid waste of palm oil (sludge) with 3 levels ie 0, 10 and 20 ton.ha-1, second factor of SP-36 fertilizer with 3 levels ie 75, 100 and 125 kg.ha-1. The data obtained were analyzed by using ANOVA and followed by HSD test at the 5 % level. The observed parameters were plant height, stem diameter, number of leaves, root canopy ratio, male flower appeared, female flower, cob diameter, ear length, cob weight per plot, weight of cob weighing and cob weight without weight. Sludge waste of 20 tons. ha-1 and fertilization of SP-36 doses 125 kg. ha-1 gave the best results for all observation parameters ie plant height, stem diameter, number of leaves, root shoot ratio, speed up male flowers appears and female flowers appear, the diameter of the ear, the length of the ear, the weight of the cob per plot, the weight of the cob weighs and the weight of the cob without the weights. Keywords: Sludge, SP-36 fertilizer, Inceptisol, sweet corn